Model Tatalaksana Komprehensif Tuberculosis Multidrug-Resistant (TB-MDR) Melalui Pendekatan Provider Pelayanan Kesehatan - Okky Haidar Yahya Irawansa; Yudha Bhaskoro; Ahmad Rizki Maulana; Febri Endra Budi Setyawan (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2020)
Introduction: Tuberculosis is a highly contagious disease and requires long-term treatment and large amounts of medication. This can affect the high risk of Multidrug-Resistant Tuberculosis (MDR-TB). A health service approach in providing comprehensive management including promotive, preventive, curative, and rehabilitative is very necessary to overcome these cases. Aim of study: This article aims to determine interventions that can be carried out by health services in preventing the occurrence of multidrug-resistant tuberculosis (MDR-TB). Method: The method used is a literature review through national to international journals that examine the interventions that can be carried out by health services in preventing MDR-TB. The articles or data sources that have been obtained will be compared with one another so that the factors that most influence the occurrence of MDR-TB can be found. Results and Discussion: The literature search results show that health workers, especially doctors, have an important role in managing MDR-TB cases. Management of MDR-TB in a comprehensive manner is carried out through promotive, preventive, curative, and rehabilitative programs through a health service provider approach. Educational activities regarding TB, MDR-TB, or the possibility of drug resistance are important to do to prevent new cases of MDR-TB. Curative treatment is carried out to improve mental and social health. Furthermore, rehabilitative efforts are carried out as a means to improve health status recovery for MDR-TB sufferers. Conclusion: Health service providers can improve facilities, they can carry out promotive, curative rehabilitative management to reduce the incidence of MDR-TB.